Batteries for Sustainability Selected Entries from the Encyclopedia of Sustainability Science and Technology - Brodd, Ralph J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Batteries that can store electricity from solar and wind generation farms are a key component of a sustainable energy strategy.   Featuring 15 peer-reviewed entries from the Encyclopedia of Sustainability Science and Technology, this book presents a wide range of battery types and components, from nanocarbons for supercapacitors to lead acid battery systems and technology.   Worldwide experts provide a snapshot-in-time of the state-of-the art in battery-related R&D, with a particular focus on rechargeable batteries.  Such batteries can store electrical energy generated by renewable energy sources such as solar, wind, and hydropower installations with high efficiency and release it on demand.  They are efficient, non-polluting, self-contained devices, and their components can be recovered and used to recreate battery systems.  Coverage also highlights the significant efforts currently underway to adapt battery technology to power cars, trucks and buses in order to eliminate pollution from petroleum combustion.  Written for an audience of undergraduate and graduate students, researchers, and industry experts, Batteries for Sustainability is an invaluable one-stop reference to this essential area of energy technology. Provides an overview of electrochemical processes and devices Features comprehensive coverage of battery types, materials, and applications Assesses efficiency and pollution output for rechargeable and non-rechargeable batteries Presents authoritative, peer-reviewed entries from the Encyclopedia of Sustainability Science and Technology.
1. Batteries, Introduction -- 2. Battery Cathodes -- 3. Battery Components, Active Materials for -- 4. Electrochemical Supercapacitors and Hybrid Systems -- 5. Lead Acid Battery Systems and Technology for Sustainable Energy -- 6. Rechargeable Batteries, Separators for -- 7. Lithium Battery Electrolyte Stability and Performance from Molecular Modeling and Simulations -- 8. Lithium-Ion Batteries, Electrochemical Reactions in -- 9. Lithium-Ion Batteries, Safety -- 10. Lithium-Ion Battery Systems and Technology -- 11. Medical Device Batteries -- 12. Nanocarbons for Supercapacitors -- 13. Nickel-Based Battery Systems -- 14. Olivine Phosphate Cathode Materials, Reactivity and Reaction Mechanisms -- 15. Silicon-Based Anodes for Li-Ion Batteries -- Index.
Keywords: Energy storage; Energy systems; Electrochemistry; Optical materials; Electronic materials; Energy Storage; Energy Systems; Electrochemistry; Optical and Electronic Materials